Restless legs syndrome affecting the head region: restless head syndrome - Balgetir, Ferhat; Gonen, Murat; Berilgen, Ayse; Aytac, Emrah; Demir, Caner Feyzi; Mungen, Bulent (Springer-Verlag Italia Srl, 2022)
Objective Restless legs syndrome (RLS) is a well-established disease that has recently been shown to have variants affecting the arms, face, abdomen, and genital area. To our knowledge, there has been no study reporting on the RLS variant affecting the head region. Methods The retrospective study reviewed a total of 460 patients who presented to Firat University Medical School and were diagnosed as having RLS based on the International Restless Legs Syndrome Study Group (IRLSSG) criteria between June 2017 and January 2020. Of these, 18 patients that presented with head-related RLS symptoms (in addition to legs or arms) and four cases that presented with isolated head involvement were included in the study. Results In 15 out of 18 (81.8%) patients, the restless head syndrome was accompanied by restless arm syndrome (RAS). In the remaining four (18.2%) patients, the disease involved the head region alone. The disease initially emerged in a single region in the body and gradually spread to one or multiple other regions in most patients and the symptoms were relieved by head rubbing. Serum iron level was low in 8 (36.4%) patients and normal in 14 (63.6%) patients. All the patients had normal cranial imaging and the symptoms were eliminated after dopaminergic therapy. Conclusions Although RLS typically involves the legs alone, it may also affect other body parts such as upper extremities, abdomen, face, and genital area. We propose that the novel RLS variant described in the present study could be termed restless head syndrome.
Keywords: Restless legs syndrome; Variant; Restless head syndrome